(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
The present study was conducted in Nishanbaria, a remote coastal village of Barguna district, Bangladesh where access to fresh water is the biggest problem due to salinity and cyclones along with poverty. The study applied several research methods (household survey, Key Informant Interviews, Focus Group Discussion, and observation) to conduct a cross-sectional analysis in order to identify the severity of the water problems and their impacts on people’s health in this village. The study reveals that drinking and using saline and dirty water for a long time have direct impacts on health; 87.9% of the families had sick members during the field survey in 2022. The major health problems are skin diseases (according to 30.65 % of the respondents), gastric problems (25.39%), and waterborne diseases (19.35%). According to 90.3% of residents, the salinity of water has a direct impact on pregnancy and children’s health and well-being. As the majority of the people collect drinking water from tube wells (80.43%), the number of people using tube wells goes down to only 24.4% after cyclones. Women are the main water collectors in this village; drinking water is collected by female members in 86.86% of the families, domestic water in 98.19%, and water for cleaning purposes in 93.56% of the families. Women are at risk of health problems; different types of pains (according to 49.36% of the residents), accidents (34.33%), and gender-based violence stem from carrying water from distant sources. Poverty (97.84% of the residents live below the poverty line) creates disparity among the residents in accessing proper treatments for all these health problems as well as collecting fresh water from distant sources. A comprehensive and context-based hazard and disaster management plan is required to help this disaster-prone village in improving freshwater availability, and their health and well-being. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 15-26